Implementation of management tools in the direction and execution of road works - Barrantes-Jiménez, Roy (2025)
This study showcases the results obtained from the application of project management tools in the direction and execution of road works in Costa Rica. Various techniques were explored, focusing on how to facilitate and optimize management. Specifically, the aim was to demonstrate the outcomes of implementing facilitation techniques such as brainstorming, option evaluation, and information exchange, as well as analytical techniques including clustering methods, root cause analysis, the five-whys method, questionnaires, and alternative generation in projects managed by the National Road Council. This study was conducted using a participatory methodology in conjunction with the main hierarchies of the National Road Council across several work sessions guided by the researchers. Additionally, a compilation of “lessons learned” from various road construction projects in Costa Rica was performed as a management tool. These analyses were carried out to highlight the utility and importance of using these techniques and management tools in road works, and their role as facilitators for continuous improvement and the pursuit of process optimization. The findings demonstrate how the use of these techniques can establish a clear roadmap towards the enhancement of road projects, incorporating basic principles of project management and identifying areas that require greater concentration of efforts, resources, or institutional restructuring.